Assessing the carotenoid profiles and allelic diversity of yellow maize inbred lines adapted to mid-altitude subhumid maize agroecology in Ethiopia - Garoma, Belay; Azimach, Girum; Bante, Kassahun; Menkir, Abebe (Frontiers in Plant Science, 2024)
Biofortification of provitamin A in maize is an attractive and sustainable remedy to the problem of vitamin A deficiency in developing countries. The utilization of molecular markers represents a promising avenue to facilitate the development of provitamin A (PVA) enriched maize varieties. We screened 752 diverse tropical yellow/orange maize lines using KASP (Kompetitive Allele-Specific PCR makers) to validate the use of KASP markers in PVA maize breeding. To this end, a total of 161 yellow/orange inbred lines, selected from among the 752 lines were evaluated for their endosperm PVA and other carotenoid compounds levels in two separate trials composed of 63 and 98 inbred lines in 2020 and 2021, respectively. Significant differences (P<0.001) were observed among the yellow maize inbred lines studied for all carotenoids contentcarotenoid profiles. An inbred line TZMI1017, introduced from International Institute of Tropical Agriculture (IITA) showed the highest level of PVA (12.99 µg/g) and β-carotene (12.08 µg/g). The molecular screening showed 43 yellow maize inbred lines carried at least three of the favorable alleles of the KASP markers. TZMI1017 inbred line also carried the favorable alleles of almost all markers. In addition, nine locally developed inbred lines had medium to high PVA concentration varying from 5.11 to 10.76 µg/g and harbored the favorable alleles of all the KASP PVA markers. Association analysis between molecular markers and PVA content variation in the yellow/orange maize inbred lines did not reveal a significant predictable correlation.Further investigation is warranted to elucidate the underlying genetic architecture of PVA content in this germplasm. However, we recommend strategic utilization of the maize inbred lines with higher PVA content to enhance the PVA profile of the breeding program's germplasm.